2013
DOI: 10.1021/ja4019379
|View full text |Cite
|
Sign up to set email alerts
|

Optically Selective Two-Photon Uncaging of Glutamate at 900 nm

Abstract: We have synthesized a 7-diethylaminocoumarin (DEAC) derivative that allows wavelength selective, two-photon uncaging at 900 nm versus 720 nm. This new caging chromophore, called DEAC450, has an extended π-electron moeity at the 3-position that shifts the absorption spectrum maximum of DEAC from 375 nm to 450 nm. Two-photon excitation at 900 nm was more than 60-fold greater than at 720 nm. Two-photon uncaging of DEAC450-Glu at 900 nm at spine heads on pyramidal neurons in acutely isolated brain slices generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
215
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(228 citation statements)
references
References 45 publications
6
215
0
7
Order By: Relevance
“…In contrast we could use G5-DEAC450-GABA at 66 μM or even 45 μM and still reliably evoke currents by 2P excitation at 900 nm (Figure 4c,d). We also confirmed that G5-DEAC450-GABA was, like previous DEAC450-caged transmitters [16,18] , essentially inactive at 720 nm (Fig. S4).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In contrast we could use G5-DEAC450-GABA at 66 μM or even 45 μM and still reliably evoke currents by 2P excitation at 900 nm (Figure 4c,d). We also confirmed that G5-DEAC450-GABA was, like previous DEAC450-caged transmitters [16,18] , essentially inactive at 720 nm (Fig. S4).…”
supporting
confidence: 87%
“…Thus, we were subsequently surprised to discover that MNI-Glu was not inert towards GABA-A receptors [14,15] . This off-target effect was substantiated by other reports and applies to other caged glutamate probes such CDNI-Glu [16] and RuBi-Glu [16,17] . Much less surprising was that caged GABA probes such as CDNI-GABA [15] , RuBi-GABA [18] and PEG-DEAC450-GABA [18] were also found to be quite antagonistic towards GABA-A receptors.…”
supporting
confidence: 74%
“…3-Carboxy derivatives of aminocoumarins are known to have absorption spectra with similar bathochromic shifts to 1-4 , 12 but we found the synthesis of such simple derivatives in a form suitable for elaboration into caged compounds surprisingly problematic (data not shown). In contrast, a functionalized DEAC-based caging chromophore could be created in a facile manner by Heck coupling of methylvinylacrylate 16 or tert -butylacrylate 11 to 5 to give the core DEAC450 chromophore (Supplemental movie). Mesylation of alcohol 8 11 gave 9 and this derivative was used to alkylate the tri-n-butylamine salt of cAMP to give 10 in 35% overall yield.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a functionalized DEAC-based caging chromophore could be created in a facile manner by Heck coupling of methylvinylacrylate 16 or tert -butylacrylate 11 to 5 to give the core DEAC450 chromophore (Supplemental movie). Mesylation of alcohol 8 11 gave 9 and this derivative was used to alkylate the tri-n-butylamine salt of cAMP to give 10 in 35% overall yield. Treatment of 10 with TFA followed by HPLC purification gave equatorial and axial derivatives 11a and 11b , in yields of 35% and 44%, respectively (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation